ASSESSMENT OF COMPLICATIONS OF GASTRODUODENAL ULCERS IN THE POPULATION OF CENTENARIANS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
To study and evaluate the features of complications of gastric ulcer and duodenal ulcer in the long-lived population.